x - 2x = -x

2x+x2x = x+xso 2x+x isx+x+x = 3x

Assuming you mean (2x) (-x) the answer is -2x^2

2X * 2X * 2X = 8X^3 2X^3 is saying 2*( X * X * X) = 2X^3

2x + 3 = x 2x + 3 - 3 = x - 3 2x = x - 3 2x - x = x - 3 - x x = -3

x+7 = 2x 2x = x+7 2x-x = 7 x = 7

(2x + 1) + (x*x - 2x + 1) = x^2 + 2x - 2x + 1 + 1 = x^2 + 2

x times 2x is 2x squared or 2x2

tan x + (tan x)(sec 2x) = tan 2x work dependently on the left sidetan x + (tan x)(sec 2x); factor out tan x= tan x(1 + sec 2x); sec 2x = 1/cos 2x= tan x(1 + 1/cos 2x); LCD = cos 2x= tan x[cos 2x + 1)/cos 2x]; tan x = sin x/cos x and cos 2x = 1 - 2 sin2 x= (sin x/cos x)[(1 - 2sin2 x + 1)/cos 2x]= (sin x/cos x)[2(1 - sin2 x)/cos 2x]; 1 - sin2 x = cos2 x= (sin x/cos x)[2cos2 x)/cos 2x]; simplify cos x= (2sin x cos x)/cos 2x; 2 sinx cos x = sin 2x= sin 2x/cos 2x= tan 2x

2x2- 2x = 2x*(x - 1)

2x-3 = x+5 2x-x = 8 x = 8

sqrt(XX) - 2x = X - 2X = -X

2x = x+3 2x-x = 3 x = 3

x+2y-2x-y=x y-x=x y=2x

x+3(x+1)=2x x + 3x + 3 = 2x 2x + 3 = 0 2x = -3 or x = -1.5

What is X if 2x + 4 = 36 What is X ? 2x + 4 = 36

Factored?2X2 - 2X2X(X - 1)================If this were set to 0, X = 0 and X = 1

f(x)=cos(sin(x2)) [u(v)]' = u'(v) * v' so f'(x) = cos'(sinx(x2)) * sin'(x2) * (x2)' f'(x) = -sin(sin(x2)) * cos(x2) * 2x = -2x sin(sin(x2)) cos(x2)

2x+x is 3x

y = 2sin(x)cos(x)Use the product rule: uv' + vu' where u is 2sin(x) and v is cos(x) to find first derivative:y' = 2sin(x)(-sin(x)) + cos(x)2cos(x)Simplify:y' = 2cos2(x)-2sin2(x)y' = 2(cos2(x)-sin2(x))Use trig identity cos(2x) = cos2(x)-sin2(x):y' = 2cos(2x)Take second derivative using chain rule:y'' = 2(-sin(2x)cos(2x))Simplify:y'' = -2sin(2x)(2)Simplify:y'' = -4sin(2x)y'' = -4sin(2x)

2x squared - 2x plus xy - y or 2x(x-1) + y(x-1) or (x-1)(2x+y)

int x ln5x dx by parts u = ln5x du = 1/5x or 5x^-1 dv = x v = 1/2x^2 uv - int v du ln5x 1/2x^2 - int 1/2x^2 5x^-1 1/2ln5x*x^2 - 1/6x^3 5x + C

y = (x^2)(sin x)(2x)(cos x) - 2sin xy' = [[(x^2)(sin x)][(2x)(cos x)]]' - (2sin x)'y' = [[(x^2)(sin x)]'[(2x)(cos x)] + [(2x)(cos x)]'[(x^2)(sin x)]]- (2sin x)'y' = [[(x^2)'(sin x) + (sin x)'(x^2)][(2x)(cos x)] + [(2x)'(cos x) + (cos x)'(2x)][(x^2)(sin x)] ] - 2(cos x)y' = [[(2x)(sin x )+ (cos x)(x^2)][(2x)(cos x)] + [2cos x - (sin x)(2x)][(x^2)(sin x)]] - 2(cos x)y' = (4x^2)(sin x cos x) + (2x^3)(cos x)^2 + (2x^2)(sin x cos x) - (2x^3)(sin x)^2 - 2cos xy' = (6x^2)(sin x cos x) + (2x^3)(cos x)^2 - (2x^3)(sin x)^2 - 2cos x (if you want, you can stop here, or you can continue)y' = (3x^2)(2sin x cos x) + (2x^3)[(cos x)^2 - (sin x)^2] - 2cos xy' = (3x^2)(sin 2x) + (2x^3)(cos 2x) - 2 cos xy' = (2x^3)(cos 2x) + (3x^2)(sin 2x) - 2 cos x

sin(2x), cos(2x), cosec(2x), sec(2x), tan(x) and cot(x) are all possible functions.

2x - 6 = x - 43 2x = x - 37 x = -37

Trending Questions

Hottest Questions

Previously Viewed

clearAsked By Wiki User

Unanswered Questions

Why did classical tradition in dance not flourish in the Philippines?

Asked By Wiki User

Ano ang mensahe ng ating pambansang awit?

Asked By Wiki User

What are the advantages and disadvantages of daisy chain topology?

Asked By Wiki User

What classification instrument of tongatong?

Asked By Wiki User

Copyright ยฉ 2021 Multiply Media, LLC. All Rights Reserved. The material on this site can not be reproduced, distributed, transmitted, cached or otherwise used, except with prior written permission of Multiply.